The TREX-DM experiment at the Canfranc Underground Laboratory. (February 2020) - Castel, J; Cebrián, S; Dafni, T; Galán, J; Irastorza, IG; Luzón, G; Margalejo, C; Mirallas, H; Ortiz de Solórzano, A; Peiró, A; Ruiz-Chóliz, E
Abstract: TREX-DM (TPC Rare Event eXperiment for Dark Matter) is intended to look for low mass WIMPs in the Canfranc Underground Laboratory (LSC) in Spain, using light elements (Ne, Ar) as target in a high pressure TPC equipped with Micromegas readouts. Here, a description of the detector, the first results from commissioning data and the expected sensitivity from the developed background model are briefly presented.